Dutch Caribbean Poetics in a Historical Perspective - Rutgers, Wim (Werkwinkel, 2018)
This article provides an overview of two hundred years of Dutch Caribbean poetics: from Eurocentrism to originality, from imitation towards creation. In the 19th century colonial poets of the ABC islands followed European examples, in the beginning of the 20th century they searched for local themes and forms, and from the last decades of the 20th and in the beginning of the 21st centuries they combined the local and the global arriving at a creative amalgam of the glocal.